Acoustic Matching Characteristics of Annular Piezoelectric Ultrasonic Sensor - LI, Haoran; HU, Yan; LI, Laibo; XU, Dongyu (Archives of Acoustics, 2022)
Using intelligent materials and sensors to monitor the safety of concrete structures is a hot topic in the field of civil engineering. In order to realize the omni-directional monitoring of concrete structural damage, the authors of this paper designed and fabricated an embedded annular piezoelectric ultrasonic sensor using the annular piezoelectric lead zirconate titanate (PZT) ceramic as a sensing element and epoxy resin as the matching and the backing layers. The influence of different matching and backing layers thickness on the acoustic characteristic parameters of the sensor were studied. The results show that the resonant frequency corresponding to the axial mode of annular piezoelectric ceramics moves toward the high frequency direction with the decrease of the height of piezoelectric ceramics, and the radial vibration mode increases as well as the impedance peak. With the thickness of the backing layer increases from 1 mm to 2 mm, the radial resolution of the annular piezoelectric ultrasonic sensor is enhanced, the pulse width is reduced by 39% comparing with the sensors which backing layer is 1 mm, and the head wave amplitude and −3 dB bandwidth are increased by 61% and 66%, respectively. When the matching layer thickness is 3 mm, the sensor has the highest amplitude response of 269 mV and higher sensitivity.